﻿The transparency challenge of blockchain in organizations - Johannes Sedlmeir; Jonathan Lautenschlager; Gilbert Fridgen; Nils Urbach (Electronic Markets, 2022)
This position paper discusses the challenges of blockchain applications in businesses and the public sector related to an excessive degree of transparency. We first point out the types of sensitive data involved in different patterns of blockchain use cases. We then argue that the implications of blockchains' information exposure caused by replicated transaction storage and execution go well beyond the often-mentioned conflicts with the GDPR's "right to be forgotten" and may be more problematic than anticipated. In particular, we illustrate the trade-off between protecting sensitive information and increasing process efficiency through smart contracts. We also explore to which extent permissioned blockchains and novel applications of cryptographic technologies such as self-sovereign identities and zero-knowledge proofs can help overcome the transparency challenge and thus act as catalysts for blockchain adoption and diffusion in organizations.
Keywords: O14; 620; Confidentiality; Data protection; Digital wallet; Distributed ledger technology; Privacy; Verifiable computation